Absence of bacterial resistance to povidone iodine. Issue 8 (August 1976) - Houang, E T; Gilmore, O J; Reid, C; Shaw, E J
Abstract : Povidone iodine is now being increasingly used in hospitals as an antiseptic. The possible habituation of bacteria to iodine was studied by serial passage of two strains of Pseudomonas aeruginosa, two strains of Escherichia coli, two strains of Klebsiella aerogenes, and one strain of Serratia marcescens in subinhibitory concentrations. After 20 passages, no significant change was observed in the minimal inhibitory concentration, minimal bactericidal concentration, and killing times between parent strains and 20th subcultures under standardized conditions.